Polycyclic aromatic hydrocarbons (PAHs) and polychlorinated biphenyls (PCBs) in sediment core MAR16-02 from the Eure River, France - Thomas Gardes; Florence Portet-Koltalo; Maxime Debret; Kevin Humbert; Romain Levaillant; Michel Simon; Yoann Copard (PANGAEA, 2020)
We measured polycyclic aromatic hydrocarbons (PAHs) and polychlorinated biphenyls (PCBs) in sediment cores (collected in two independant ponds) to study the relationships between sediment deposits characteristics and organic contaminants, and the temporal trends of PAHs and PCBs were reconstructed since 1940s in the Eure River watershed, major tributary of the Seine estuary (France).